Spatial analysis of benthic functional biodiversity in san jorge gulf, Argentina - Kaminsky, Julieta (2019)
Anthropogenic pressures on coastal and marine ecosystems are increasing. Current development of spatiotemporal models will improve understanding of how changes to biodiversity distribution resulting from such pressures might affect ecosystem functioning. The objective of this study was to characterize the spatial distribution of benthic biodiversity in San Jorge Gulf (Argentina) to provide insight into the relationship between benthic habitats and biodiversity. First, we characterized the spatial heterogeneity of both sediment types and bottom water variables. Then, we described the ecosystem’s functional diversity considering trophic interactions and behavioral and morphological characteristics of benthic organisms, and we explored whether benthic environment variables can predict functional diversity distribution. Our results showed that the distribution of assemblages of epifauna functional groups in San Jorge Gulf is mainly related to oxygen availability in bottom water and organic matter in sediments. Habitat suitability maps enable us to predict this distribution, improving our knowledge of biodiversity-ecosystem functioning in the gulf, and providing information for designing sustainable management and conservation strategies for ocean ecosystem services.